2016
DOI: 10.7755/fb.114.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Fish assemblages on the southeastern Brazilian Bight, sampled by midwater trawl during spring and summer seasons: species composition, abundance, and environmental drivers

Abstract: Abstract-We provide an overall description of the species composition and abundance of pelagic fish assemblages sampled with midwater trawls at depths <100 m in the southeastern Brazilian Bight (SBB, south-southeastern Brazil) during the spring-summer period from 1995 through 2010. We also investigated the effect of 1) 3 water masses, the South Atlantic Central Water (SACW), Coastal Water (CW), and Mixed Water (M), and 2) a set of environmental and spatial variables on the SBB pelagic fish assemblages. The agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…in the ECOSAR II teams' sampling networks suggests that the consumption of teleost fish by S. brasiliensis occurred after capture and not in their natural habitat. This justification can also be associated with the data found by Contente and Rossi-Wongtschowski (2016) that show the presence of Bregmaceros atlanticus in ECOSAR cruises with a total frequency of occurrence of 2.2. Thus, it may have been captured simultaneously with S. brasiliensis.…”
Section: Diet Of Pelagic Fishessupporting
confidence: 79%
See 2 more Smart Citations
“…in the ECOSAR II teams' sampling networks suggests that the consumption of teleost fish by S. brasiliensis occurred after capture and not in their natural habitat. This justification can also be associated with the data found by Contente and Rossi-Wongtschowski (2016) that show the presence of Bregmaceros atlanticus in ECOSAR cruises with a total frequency of occurrence of 2.2. Thus, it may have been captured simultaneously with S. brasiliensis.…”
Section: Diet Of Pelagic Fishessupporting
confidence: 79%
“…In order to collect specimens, 26 hauls were conducted during the survey using a midwater trawl from which 24 caught pelagic fish. The survey was carried out on pre-established stations during the day and night, at a mean speed of 10 knots (Contente and Rossi-Wongtschowski, 2016). Particular details on the grid sampling, methods of acoustic data, and procedures of fishing operations were described in Soares et al (2005), Madureira and Rossi-Wongtschowski et al (2005), and Contente and Rossi-Wongtschowski (2016).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species exhibits a well‐defined reproductive season, with distinct periods of gonadal maturation and spawning, and its reproductive cycle overlaps with that of S. brasiliensis , indicating potential interspecies interactions and competition for resources during these periods (Petermann & Schwingel, 2016). During the spring–summer period from 1995 to 2010, data from midwater trawls in the SBB showed that O. oglinum was one of the most abundant species and strongly associated in the combination of the Coastal Water and areas of mixing between Coastal Water and South Atlantic Central Water, alongside two other clupeiform species, S. brasiliensis and Harengula clupeola (Cuvier, 1829) Contente & Rossi‐Wongtschowski, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The species exhibits a well-defined reproductive season, with distinct periods of gonadal maturation and spawning, and its reproductive cycle overlaps with that of S. brasiliensis, indicating potential interspecies interactions and competition for resources during these periods (Petermann & Schwingel, 2016). During the spring-summer period from 1995 to 2010, data from midwater trawls in the SBB showed that O. oglinum was one of the most abundant species and strongly associated in the combination of the Coastal Water and areas of mixing between Coastal Water and South Atlantic Central Water, alongside two other clupeiform species, S. brasiliensis and Harengula clupeola (Cuvier, 1829) Contente & Rossi-Wongtschowski, 2016. The Brazilian fishing industry experienced significant growth in the 1960s, primarily focusing on highly productive pelagic and demersal resources (Paiva, 1997). However, overfishing and the subsequent decline in fish stocks have led to a notable decrease in productivity, resulting in the necessity of implementing conservation policies (Dias-Neto, 2010;Freire et al, 2015).…”
mentioning
confidence: 99%